Immunohistochemical Character of Hepatic Angiomyolipoma: For Its Management - Yuka Kobayashi; Kenya Kamimura; Minoru Nomoto; Soichi Sugitani; Yutaka Aoyagi (Case Reports in Medicine)
Hepatic angiomyolipoma (AML) is notoriously difficult to diagnose without an invasive surgery even with the recent development of the various imaging modalities. Additionally, recent reports showed its malignant behavior after the surgery; it is important to diagnose the character of each tumor including the possible malignant potential and determine the postoperative management for each case. For this purpose, we have reviewed reports and focused on the immunohistochemical staining with p53 and ki67 of the tumors showing the representative case of 60-year-old female. The imaging study of her tumor showed the character similar to the hepatocellular carcinoma, and she underwent the hepatectomy. The resected tumor stained positive for HMB-45 that is a marker of the AML, and 30–50% of the tumor cells were positively stained with Ki67 that is a mitotic marker. Also, the atypical epithelioid cells displayed p53 immunoreactivity. These results suggest the malignant potential of our tumor based on the previous reports; therefore the careful followup for this case is necessary for a long period whether it shows metastasis, sizing up, and so forth.